A mass and solute balance model for tear volume & osmolarity in the normal and the dry eye - Gaffney, E; Tiffany, J; Yokoi, N; Bron, A (Elsevier, 2010)
Tear hyperosmolarity is thought to play a key role in the mechanism of dry eye, a common symptomatic condition accompanied by visual disturbance, tear film instability, inflammation and damage to the ocular surface. We have constructed a model for the mass and solute balance of the tears, with parameter estimation based on extensive data from the literature which permits the influence of tear evaporation, lacrimal flux and blink rate on tear osmolarity to be explored. In particular the nature of compensatory events has been estimated in aqueous-deficient (ADDE) and evaporative (EDE) dry eye. The model reproduces observed osmolarities of the tear meniscus for the healthy eye and predicts a higher concentration in the tear film than meniscus in normal and dry eye states. The differential is small in the normal eye, but is significantly increased in dry eye, especially for the simultaneous presence of high meniscus concentration and low meniscus radius. This may influence the interpretation of osmolarity values obtained from meniscus samples since they need not fully reflect potential damage to the ocular surface caused by tear film hyperosmolarity. Interrogation of the model suggests that increases in blink rate may play a limited role in compensating for a rise in tear osmolarity in ADDE but that an increase in lacrimal flux, together with an increase in blink rate, may delay the development of hyperosmolarity in EDE. Nonetheless, it is predicted that tear osmolarity may rise to much higher levels in EDE than ADDE before the onset of tear film breakup, in the absence of events at the ocular surface which would independently compromise tear film stability. Differences in the predicted responses of the pre-ocular tears in ADDE compared to EDE or hybrid disease to defined conditions suggest that no single, empirically-accessible variable can act as a surrogate for tear film concentration and the potential for ocular surface damage. This emphasises the need to measure and integrate multiple diagnostic indicators to determine outcomes and prognosis. Modelling predictions in addition show that further studies concerning the possibility of a high lacrimal flux phenotype in EDE are likely to be profitable.